2021
DOI: 10.3389/fcvm.2021.810791
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Glucose Cotransporter 2 Inhibitors and Heart Failure: A Bedside-to-Bench Journey

Abstract: Type 2 diabetes mellitus (T2DM) and heart failure (HF) are multifactorial diseases sharing common risk factors, such as obesity, hyperinsulinemia, and inflammation, with underlying mechanisms including endothelial dysfunction, inflammation, oxidative stress, and metabolic alterations. Cardiovascular benefits of sodium-glucose cotransporter 2 (SGLT2) inhibitors observed in diabetic and non-diabetic patients are also related to their cardiac-specific, SGLT-independent mechanisms, in addition to the metabolic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Currently, several molecular and cellular mechanisms by which SGLT2-i protects the CV system have been identified ( 47 49 ). The reduction of oxidative stress is considered a potential mechanism for the suppression of cardiac remodeling by SGLT2-i, by balancing abnormal Na + and Ca 2+ levels and protecting mitochondrial function ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several molecular and cellular mechanisms by which SGLT2-i protects the CV system have been identified ( 47 49 ). The reduction of oxidative stress is considered a potential mechanism for the suppression of cardiac remodeling by SGLT2-i, by balancing abnormal Na + and Ca 2+ levels and protecting mitochondrial function ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Later, it was found that dapagliflozin and canagliflozin inhibited Na + /H + exchanger activity and reduced cytosolic Na + [ 73 ]. Additionally, empagliflozin reduced Ca 2+ /calmodulin-dependent kinase II (CaMKII) activity and CaMKII-dependent sarcoplasmic reticulum Ca 2+ leak [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of SGLT2is against the cardiovascular (CV) and renal complications of T2DM appear to be independent of their glucose-lowering activity, with particular value being demonstrated in the reduction of risk regarding hospitalisation for heart failure (HHF) and progression of diabetic kidney disease (DKD) as well as lowering the incidence of major adverse cardiovascular events (MACE) [ 4 36 ]. Recently published reviews have described and explored the putative mechanisms underlying the cardiorenal benefits of SGLT2is, emphasising the direct and indirect effects that these medicines have on pathways that mediate inflammation, oxidative stress and endothelial cell dysfunction [ 37 , 38 ].…”
Section: The Clinical Effects Of Sglt2i Therapies: From Glucose-lower...mentioning
confidence: 99%